Teaching Architecture and Urban Design: Project for whom? (ARQUISUR Revista, 2022)
This paper aims to reinforce the importance of the idea of 'project for whom' through the approach of the ‘Environment and Behavior’ study area in the teaching of architectural and urban design, consolidated for more than 20 years in a class of the Introduction to Architectural Design II (IPA II), located on the 2nd. Semester of the Architecture and Urbanism Course at the Faculty of Architecture of the Federal University of Rio Grande do Sul (UFRGS). Thus, the methodological procedures used in the discipline include the presentation and discussion of concepts, aiming at the formation of a repertoire for the student, carrying out analyses, assessments and syntheses. Among the concepts discussed are those related to aesthetics and architectural composition, the function and insertion of the building in its context, based on theories and research results on the relationship between the built environment and its users. The analyzes and evaluations include those carried out in class, based on certain architectural designs, as well as through two exercises, while the syntheses are contained in two other exercises, including the design of a residence based on the needs of the residents of an existing house selected by the student and in the architectural, urban and geographic characteristics of the area where this house is located, connecting the student with reality. Among the results obtained is the fact that the designs carried out by the students tend to have a greater aesthetic and functional quality than the designs of the selected houses, many of which were elaborated by architects.
Keywords: Teaching architecture. Teaching urban design. Users.